Inactivation of 12 viruses by heating steps applied during manufacture of a hepatitis B vaccine - Lelie, P. N. (J Med Virol, 2005)
The efficacy of two heating cycles (90 sec at 103°C and 10 hr at 65°C) used during manufacture of a plasma‐derived hepatitis‐B vaccine was validated for the inactivation of 12 virus families. A period of 15 min warming up to 65°C had already completely inactivated representatives of nine virus families, ie, poxvirus (vaccinia), picornavirus (encephalomyocarditis virus), togavirus (sind bis virus), coronavirus (mouse hepatitis virus), orthomyxovirus (influenza virus), rhabdovirus (vesicular stomatitis virus), herpes virus (cytomegalovirus), lentivirus (human immunodeficiency virus), and retrovirus (murine leukemia virus). After prolonged heating at 65°C or heating for 90 sec at 103°C, parvovirus (canine parvovirus) and the phage phiX174 were also completely inactivated. Papovavirus represented by simian virus 40 (SV‐40) was the most heat‐resistant virus evaluated. The infectivity of SV‐40 was reduced by 10(4) Tissue Culture Infectious Doses (TCID(50)) per ml after 90 sec at 103°C, but a marginal residual activity (<5 TCID(50) per ml) was observed. Subsequent pasteurization for 10 h at 65°C did not further reduce the infectivity of SV‐40. This study shows that the two heat‐inactivation steps used during the production of this vaccine kill a wide variety of viruses that might be present in human blood.